Challenges faced by young women with premarital pregnancy: a qualitative exploration through a multiple-case study - Hizlinda Tohid,; Noor Azimah Muhammad,; Naemah Sharifuddin,; Wan Fadhilah Wan Ismail,; Rosdina Abdul Kahar,; Nafiza Mat Nasir,; Nazrila Hairizan Nasir,; Nik Rubiah Rashid,; Khairani Omar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Unplanned and unwanted pregnancy is a challenging life event, especially to young unmarried women in Malaysia as they often left unsupported. Using theory of resilience, this study aimed to explore challenges faced by non-institutionalised young unmarried women who decided to keep their pregnancy. By understanding their challenges, we could recognise their main needs for planning of effective strategies and policies that can help them to cope better with their pregnancy and prepare for their future. This was a qualitative exploration study using a multiple-case study design. Five pregnant women recruited from two primary care clinics, aged 18 years and above, with different life experiences and at different trimester underwent in-depth interviews. Data was examined using thematic analysis and compared across the five cases. The main challenges during pregnancy faced by the unmarried women were: (1) avoiding social stigma, (2) having poor psychosocial support from family, and (3) preparing for future. They were worried about financial security, childcare, illegitimate status of their child, housing arrangement and stable employment. Thus, they need to be supported in these areas. Although these young women in the community appeared to be self-reliant, independent and strong minded, they need to be supported especially from their own family members, parents, peers, health care providers and organisation for a better future for them and their children.